2019
DOI: 10.1111/ans.15383
|View full text |Cite
|
Sign up to set email alerts
|

Splenic autotransplantation: a systematic review

Abstract: Background: Splenectomy is a surgical procedure indicated in a variety of medical conditions including trauma. Postoperatively, there is a lifelong risk of developing overwhelming sepsis from encapsulated bacteria, most commonly due to Streptococcus pneumoniae. Splenic autotransplantation has been proposed as a method to recover splenic function in patients requiring splenectomy with otherwise normal spleens. This paper aims to systematically review the literature to determine the efficacy of spleen autotransp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 44 publications
1
17
0
1
Order By: Relevance
“…This is confirmed by many reports, according to which autotransplantation of the spleen is accompanied by less pronounced immunohematological changes, compared with splenectomy, but is inferior to organ-sparing operations [11]. At the same time, according to the literature, removal of 90 % of the spleen does not lead to the development of hyposplenism [12]. The presented data significantly changed the tactics in the management of the diseases of the spleen.…”
supporting
confidence: 77%
“…This is confirmed by many reports, according to which autotransplantation of the spleen is accompanied by less pronounced immunohematological changes, compared with splenectomy, but is inferior to organ-sparing operations [11]. At the same time, according to the literature, removal of 90 % of the spleen does not lead to the development of hyposplenism [12]. The presented data significantly changed the tactics in the management of the diseases of the spleen.…”
supporting
confidence: 77%
“…3,4,9 Most studies implanted slices of the spleen or minced splenic tissue into the omentum, which made them more prone to ischaemia from torsion of the omentum, trauma, and bleeding or intestinal obstruction. 9 Di Carlo et al 5 have proposed a new technique for implanting a single segment of the spleen (approximately 25-30 cm 3 in size) in the native site of the original spleen and fixed to it. In this way, the implanted splenic tissue would be protected by the rib cage, and the risk of traumatic bleeding, intestinal obstruction or torsion of the omentum significantly decreases.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the implanted splenic tissues could offer patients protection against infection by encapsulated bacteria or prevent OPSI is yet to be confirmed. 9,12 Some studies have reported the occurrence of fatal OPSI in patients with splenosis or implanted splenic tissues despite receiving pneumococcal vaccination. Nevertheless, they were case reports published four decades ago.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations